2023
DOI: 10.1186/s12974-023-02787-w
|View full text |Cite
|
Sign up to set email alerts
|

Pathological hemodynamic changes and leukocyte transmigration disrupt the blood–spinal cord barrier after spinal cord injury

Abstract: Background Blood–spinal cord barrier (BSCB) disruption is a key event after spinal cord injury (SCI), which permits unfavorable blood-derived substances to enter the neural tissue and exacerbates secondary injury. However, limited mechanical impact is usually followed by a large-scale BSCB disruption in SCI. How the BSCB disruption is propagated along the spinal cord in the acute period of SCI remains unclear. Thus, strategies for appropriate clinical treatment are lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Therefore, further research is needed to develop diagnostic and predictive prognostic models for acute TSCI, and a framework for identifying valuable biomarkers is also necessary to improve the accuracy of prognostic prediction. It has been shown that the blood-spinal cord barrier (BSCB) is disrupted by TSCI, leukocyte tra cking is also increased (21,22). Some in ammatory biomarkers, such as C-reactive protein (CRP ), IL-6 or monocyte chemotactic protein-1, can participate in the systemic in ammatory response and can be transported into the blood or cerebrospinal uid(8, 23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further research is needed to develop diagnostic and predictive prognostic models for acute TSCI, and a framework for identifying valuable biomarkers is also necessary to improve the accuracy of prognostic prediction. It has been shown that the blood-spinal cord barrier (BSCB) is disrupted by TSCI, leukocyte tra cking is also increased (21,22). Some in ammatory biomarkers, such as C-reactive protein (CRP ), IL-6 or monocyte chemotactic protein-1, can participate in the systemic in ammatory response and can be transported into the blood or cerebrospinal uid(8, 23,24).…”
Section: Discussionmentioning
confidence: 99%
“…After the disruption of the blood-spinal cord barrier, significant leakage can occur, reaching its peak at 24 h post-injury and showing a second peak on the fifth day ( Chang and Cao, 2021 ). It was found that most of the leakage occurs in the pericellular space, and intercellular pathways are less common, with TJ proteins being the main component connecting BSCB cells ( Zhou et al, 2023 ). The study of He et al (2023) indicates that spinal cord injury can induce lysosomal damage, leading to disruption of the endothelial cell autophagic flow and dysfunction of the autophagy-lysosomal pathway (ALP).…”
Section: The Mechanisms Underlying Disruption Of the Blood-spinal Cor...mentioning
confidence: 99%
“…Studies have shown that there is no significant decrease in TJ proteins in the early stages of spinal cord injury, specifically at the 1st and 3rd hours. However, a significant reduction can be observed from the 8th to the 24th hour ( Zhou et al, 2023 ). The decrease in TJ expression, along with changes in TJ localization or post-transcriptional modifications, are the main reasons leading to an increased permeability of the BSCB ( Deli et al, 2005 ; Chio et al, 2019 ; Zhou et al, 2023 ).…”
Section: The Mechanisms Underlying Disruption Of the Blood-spinal Cor...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 These exudates trigger a cascade of complex pathological processes including neurotoxic product generation, oxidative stress response, and inflammatory cell infiltration, resulting in the programmed death of neurons at lesions and interface of the injury site that may even lead to permanent neurological deficits. 3,4 Notably, the loss of BSCB integrity is detrimental to the maintenance of homeostasis of the internal environment of the spinal cord, and it also impacts the generation of blood vessels that act as a scaffold for axonal regeneration. 5,6 Thus, it is significant to target BSCB repair at an early stage of SCI to mitigate peri-lesional cellular perturbations and thereby modulate neuronal network homeostasis.…”
Section: Introductionmentioning
confidence: 99%